2022
DOI: 10.1097/cad.0000000000001372
|View full text |Cite
|
Sign up to set email alerts
|

Defibrotide suppresses brain metastasis by activating the adenosine A2A receptors

Abstract: Brain metastasis is a devastating clinical condition globally as one of the most common central nervous system malignancies. The current study aimed to assess the effect of defibrotide, an Food and Drug Administration-approved drug, against brain metastasis and the underlying molecular mechanisms. Two tumor cell lines with high brain metastasis potential, PC-9 and 231-BR, were subjected to defibrotide treatment of increasing dosage. The metastasis capacity of the tumor cells was evaluated by cell invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Defibrotide is a polydisperse polydeoxyribonucleotide that has thrombolytic effects that are beneficial for the hypercoagulable sequelae of cancer states, and it also demonstrated anti‐tumor activity when used as a single agent against multiple myleoma 8 . Recently, Dong et al 9 has shown defibrotide to modulate brain metastasis through inhibition of “proliferation, migration, invasion, and promotion of lactate dehydrogenase release of brain metastatic tumor cells, and elevation of the levels of blood brain barrier tight junction proteins and metastasis‐related proteins” via activation of adenosine A2A receptors and downstream inhibition of the SDF‐1/CXCR4 axis. Lastly, defibrotide was shown to have anti‐angiogenic properties after inhibiting the formation of new blood vessels during in‐vitro and in‐vivo studies and was postulated for use as an adjuvant anti‐cancer therapeutic 10 .…”
Section: Case Reportmentioning
confidence: 99%
“…Defibrotide is a polydisperse polydeoxyribonucleotide that has thrombolytic effects that are beneficial for the hypercoagulable sequelae of cancer states, and it also demonstrated anti‐tumor activity when used as a single agent against multiple myleoma 8 . Recently, Dong et al 9 has shown defibrotide to modulate brain metastasis through inhibition of “proliferation, migration, invasion, and promotion of lactate dehydrogenase release of brain metastatic tumor cells, and elevation of the levels of blood brain barrier tight junction proteins and metastasis‐related proteins” via activation of adenosine A2A receptors and downstream inhibition of the SDF‐1/CXCR4 axis. Lastly, defibrotide was shown to have anti‐angiogenic properties after inhibiting the formation of new blood vessels during in‐vitro and in‐vivo studies and was postulated for use as an adjuvant anti‐cancer therapeutic 10 .…”
Section: Case Reportmentioning
confidence: 99%